KESANTUNAN BERBAHASA WARGANET DALAM KOMENTAR AKUN INSTAGRAM @PSSI: TINJAUAN PRAGMATIK - hartono, budi; Masnita Massaguni (An-Nas, 2025)
Social media has become a dynamic space for public discourse, including in Indonesia. Instagram, particularly official accounts such as @PSSI, is often used by netizens to express opinions, criticism, and support related to national football issues. This phenomenon reflects the complexity of digital communication, which is rich in social values and linguistic politeness. This study aims to identify the forms of linguistic politeness employed by netizens in the comment section of the official Instagram account @PSSI. The research adopts a pragmatic approach, referring to Leech’s politeness maxims, which include the maxims of tact, generosity, approbation, modesty, agreement, and sympathy. This qualitative descriptive study utilizes documentation and note-taking techniques on relevant user comments collected between February and June 2025. The analysis reveals that netizens continue to apply various politeness maxims in conveying criticism, support, and expressions of solidarity in a respectful manner. These comments demonstrate ethical communication strategies, including motivation, advice, sympathy, and collective appeals. The findings affirm that the digital space, despite its vulnerability to negative speech, can serve as a platform for constructive and civil expression. This research contributes to the development of pragmatic studies and offers practical insights for public institutions in managing social media communication.